Internalization of Braya's Amazing Values as A Management of Business Control In Endek Clothing UKM and Klungkung Songket (Case Study Approach) - Adnyani, Ni Ketut Sari; Purnamawati, I Gusti Ayu; Sulindawati, Ni Luh Gede Erni (UNIVERSITAS NEGERI SURABAYA, 2019)
The research study in this article is in the form of values of Brama as a social capital in the development of creative industries by the craftsmen who are members of Small and Medium Enterprises (SMEs) crafts of endek ikat and songket Klungkung. Values align Braya to SME leadership patterns, human relationships with other SMEs, workers, and customers, and social responsibility in order to provide welfare to their workers. Research method, This research use model (Research and Development). The sample of 15 SMEs involved in the develompment stage was chosen purposively. Needs analysis was conducted as a basis for designing an evaluation model of the planting of values of Braya based on local genius. Outcomes: Braya's Branding Values Internalized by SMEs, their relevance influences SMEs' social responsibility attitude, combines empowerment and entrepreneurship aspects based on kinship and togetherness